An exploratory study on the physical manifestations of selected religions in selected Chinese Filipino variety stores in Chinatown - Ferrer, Mary Joyce C.; Faustino, Johanna Victoria Acab. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Chinese Filipinos view religion as an important factor in building their business. With that in mind,the purpose of the study is to explore the physical manifestations of selected religions within the interiors of selected Chinese Filipino variety stores in Chinatown. The study also sought to discover the different ways of manifestations in which owners practice their religion, as well as, the reasons behind it through a study focusing on the store layout and the display of religious items. An exploratory approach was utilized to discover the religious physical manifestations found within the stores. The study used both qualitative and quantitative research methods through surveys and interviews, to get the data from 20 respondents. Respondents were Chinese Filipino owners of variety stores located in Chinatown. The variety stores were also documented, through pictures of the interiors and block floor plans of the store layouts. In the study, the practice of religion was manifested through (1) placing religious objects within the stores, found mostly in the selling area, and (2) by creating a space for these religious objects. Generally, the respondents practice incense burning and offerings to thank and respect their gods. The statue of Tu Di Gong and Guan Gong, the statue of Santo Niño, and censers - where incense is placed, are among the most common religious items found. These findings show that religion is significant to the respondents, because they believe that religion within the store allows their business and spirituality to grow, thereby improving their quality of life. Religion is also reflected in the interior spaces of the stores because there are certain religious beliefs and practices which require a physical manifestation, such as incense burning and offerings.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Business -- Religious aspects; Variety stores -- Philippines -- Interior decoration